Female urinary incontinence – should we always perform surgery? - Rechberger, Tomasz; Tomaszewski, Jacek; Adamiak, Aneta (Menopause Review/Przegląd Menopauzalny, 2005)
There are a lot of factors engaged in the etiopathogenesis of urinary incontinence. The algorythym of diagnosis and treatment of female urinary incontinence is very complicated. The sufficient terapeutic options is dependent on proper diagnosis. The surgery procedures as more invasive to patients always should be preceeded by trial of conservative therapy.